2016
DOI: 10.1111/srt.12278
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of neural and vascular hyper‐reactivity for sensitive skin

Abstract: The sensitive subjects were prone to be stimulated by capsaicin to trigger neural and vascular hyper-reactivity. The genetic variation of TRPV1 and the unpleasant sensation demonstrate that TRPV1 play an important role in the pathogenesis of sensitive skin. Our study supports that sensory irritation inhibitors and anti-inflammatory compounds should be considered to be added in cosmetics to reduce the heighted neural and vascular reaction of sensitive skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…There was also no correlation between age and heat pain threshold (not shown), in concordance with previous findings [23]. Studies on people with different hair colour revealed significant differences in the heat pain threshold of black haired and red haired by 1.4°C [24] and recent studies strengthened a potential genetic influence of SNPs in the TRPV1 receptor gene [9]. Skin inflammation was shown to be associated with the release of inflammatory and nociceptive mediators and resulted in significant tissue hyperalgesia in case of UV-B-induced sunburn [25] with a reduction of the heat pain threshold by 6°C.…”
Section: Discussionsupporting
confidence: 88%
“…There was also no correlation between age and heat pain threshold (not shown), in concordance with previous findings [23]. Studies on people with different hair colour revealed significant differences in the heat pain threshold of black haired and red haired by 1.4°C [24] and recent studies strengthened a potential genetic influence of SNPs in the TRPV1 receptor gene [9]. Skin inflammation was shown to be associated with the release of inflammatory and nociceptive mediators and resulted in significant tissue hyperalgesia in case of UV-B-induced sunburn [25] with a reduction of the heat pain threshold by 6°C.…”
Section: Discussionsupporting
confidence: 88%
“…A total of 60.8% of the population were of female gender. The median age was 43 (range: 16–78) years and the majority of subjects were Caucasian (96.3%) and were originally Dutch (86.4%); (the latter being 79.2% in the Netherlands). Fitzpatrick skin type distribution was: skin type I: 5.3%; II: 32.6%; III: 44.7%; IV: 15.5%; V: 1.9%; VI: 0.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have recently performed and showed that sensitive skin subjects have lower nerve fibre densities and increased expressions of transient receptor potential vanilloid‐1 . Sensitive subjects were more easily showing vascular hyperreactivity and sensations following capsaicin application . Yet, the physiological reality and contribution of each of these in SS lacks thorough understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of sensitive skin consists of an inflammatory reaction resulting from the abnormal penetration in the skin of potentially irritating substances, due to skin barrier dysfunction and changes in the production of local neuromediators . The results of many researches showed significant lower sensory perception value of sensitive skin group compared with healthy control group . Several studies have suggested a link between sensitive skin and a disruption of the epidermal barrier function, resulting in the perception of skin discomfort .…”
Section: Discussionmentioning
confidence: 99%
“…Subjects rested for 30 min in an environment‐controlled room (temperature 20 ± 2°C, relative humidity 40–60%) after cleaning face with water and drying gently with paper towels. Then, we used a solution of 10% aqueous lactic acid (50 μL) on nasolabial fold through two layers of filter paper (0.8 cm diameters) randomly . Another solution was used distilled water on the other side.…”
Section: Participants and Methodsmentioning
confidence: 99%